Islam dan Negara: Analisis Perlindungan Hukum Terhadap Hak Cuti Pekerja Wanita Dalam Undang-Undang Nomor 6 Tahun 2023 Tentang Ketenagakerjaan - Rahma Fitri, Maisyithoh; Mumtazinur, Mumtazinur; Mubarak, Husni (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2024)
Law Number 6 of 2023 on Employment provides a strong legal foundation for upholding the rights of female workers, including the right to menstrual leave. This study delves into the right to menstrual leave from the perspective of Fiqh Siyasah within the context of the principle of Mabda al-Musawah (equality) and responsive law. This principle emphasizes the importance of equal treatment without gender discrimination and the need for laws that are responsive to social changes to ensure regulations can protect the rights of female workers and create an inclusive work environment. In Islamic law, the principles of mabda al-musawah and responsive law underscore the importance of justice for female workers and emphasize equality before the law regardless of gender. The research method involves literature studies with qualitative descriptive analysis. The results of the study show that the principle of mabda al-musawah emphasizes the importance of equality and fair treatment for all workers without gender discrimination and provides opportunities for female workers to rest without losing their right to wages. The principle of responsive law emphasizes the adaptability of laws to social changes and community needs, which is relevant to the specific needs of female workers related to the menstrual cycle. Thus, it can be concluded that the implementation of the principles of mabda al-musawah and responsive law in menstrual leave rights is not explicitly regulated, indicating that the law does not adequately meet the needs of female workers. Additionally, the payment of wages during leave, which depends on agreements with employers, can disadvantage workers. The legislative process that lacks the involvement of society, especially workers and women, shows that this law is not fully responsive